(untitled) (Anclajes, 2017)
In the theoretical framework in which historiographical discourse is defined as a narrative construct and therefore, essentially ideological, the problem of writing the Crónica de tres reyes (a mid-14th century Castilian text attributed to Sánchez de Valladolid) is approached from a perspective that seeks to investigate ideological suppositions that may have influenced the design of a discourse different from that of previous royal and noble chronicles. Likewise, the issue concerning the marginal notes present in the handwritten tradition is approached as inscriptions of tension with regard to the authoritative narrative voice of the chronicler’s text.